PERFORMANCE OF NEWLY CONFIGURED SUBMERGED MEMBRANE BIOREACTOR FOR AEROBIC INDUSTRIAL WASTEWATER TREATMENT - I Gede Wenten (Reaktor, 2009)
The application of membrane to replace secondary clarifier of conventional activated sludge, known as membrane bioreactor, has led to a small footprint size of treatment with excellent effluent quality. The use of MBR eliminates almost all disadvantages encountered in conventional wastewater treatment plant such as low biomass concentration and washout of fine suspended solids. However, fouling remains as a main drawback. To minimize membrane fouling, a new configuration of submerged membrane bioreactor for aerobic industrial wastewater treatment has been developed. For the new configuration, a bed of porous particle is applied to cover the submerged ends-free mounted ultrafiltration membrane. Membrane performance was assessed based on flux productivity and selectivity. By using tapioca wastewater containing high organic matter as feed solution, reasonably high and stable fluxes around 11 l/m2.h were achieved with COD removal efficiency of more than 99%. The fouling analysis also shows that the newly configured ends-free membrane bioreactor exhibits lower irreversible resistance compared with the submerged one. In addition, the performance of pilot scale system, using a membrane module  with 10 m2 effective area and reactor tank with 120 L volume, was also assessed. The flux achieved from the pilot scale system around 8 l/m2.h with COD removal of more than 99%. Hence, this study has demonstrated the feasibility of the newly configured submerged ends-free MBR at larger scale.